دراسة تأثير المواد المالئة (TiO2 - CaCO3) على الخواص الميكانيكية لمركبات البولي أوريثان المطاطي - خضر خفيف; رامي منصور; لبنى أحمد خليل (Tishreen University, 2019)
This paper aims to study the effect of fillers (TiO2 - CaCO3) on the mechanical properties of elastomer polyurethane. To achieve this aim, samples were prepared by using different percentages (0 - 35) % of dioxide titanium (TiO2) and calcium carbonate (CaCO3), After that the Mechanical tests were carried out on these samples. The results showed that there were remarkable improvement in mechanical properties by increasing the percentage of fillers according to their types in polyurethane, and demonstrated that dioxide titanium more effective than Calcium carbonate for increasing tensile strength and  hardness while calcium carbonate more effective in increasing stiffness. دراسة تأثير المواد المالئة (TiO2 - CaCO3) على الخواص الميكانيكية لمركبات البولي أوريثان المطاطي يهدف البحث إلى دراسة تأثير المواد المالئة (TiO2 - CaCO3) على الخواص الميكانيكية لمادة البولي أوريثان المطاطي. لتحقيق هذا الهدف قمنا بتحضير عينات الاختبار من البولي أوريثان المطاطي الحاوية على مواد مالئة بنسب مختلفة تتراوح ضمن المجال من0 - 35) %  ) من ثاني أوكسيد التيتانيوم (TiO2) وكربونات الكالسيوم (CaCO3) ودراسة تأثير النسب المضافة على الخواص الميكانيكية. أظهرت نتائج الاختبارات تحسناً ملحوظاً في الخواص الميكانيكية المدروسة بزيادة نسبة المادة المالئة وفقاً لنوعيتها في البولي أوريثان, حيث تبين أن ثاني أوكسيد التيتانيوم أكثر تأثيراً من كربونات الكالسيوم بزيادة مقاومة الشد والقساوة في حين أن كربونات الكالسيوم أكثر تأثيراً في زيادة الصلابة.